Green synthesis, biomedical effects, and future trends of Ag/ZnO bimetallic nanoparticles: An update - Zhang Shengai; Chen Jia; Ma Yiwei; Zhao Qinghua; Jing Bo; Yu Mingli; Yang Na; Yang Aili; Shen Qingqing; Wang Yuyan; Yang Haiyan; Zhao Chunhai (Nanotechnology Reviews)
Nanomaterials possess unique properties that make them highly valuable in biomedical applications. However, traditional physical and chemical synthesis methods suffer from significant drawbacks, including high energy consumption, environmental pollution, and inconsistent performance. In contrast, green synthesis offers an eco-friendly, cost-effective, and sustainable alternative, making it an emerging research focus in nanomaterial development. The green synthesis of plant-derived silver/zinc oxide (Ag/ZnO) bimetallic nanoparticles has gained considerable attention due to their promising biomedical applications. This review systematically examines the green synthesis, characterization, and biomedical potential of plant-derived Ag/ZnO bimetallic nanoparticles. The goal is to provide a comprehensive framework for advancing eco-friendly synthesis techniques, optimizing nanoparticle properties, and facilitating their practical application in biomedicine. This systematic review adhered to the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines. A comprehensive analysis of peer-reviewed studies published up to November 18, 2024, was conducted, focusing on the green synthesis, physicochemical properties, and biomedical applications of Ag/ZnO bimetallic nanoparticles. A structured literature search was performed across Web of Science, Scopus, PubMed, Cochrane Library, and ScienceDirect using Boolean operators to combine key terms such as “green synthesis,” “Ag/ZnO nanoparticles,” and “biomedical applications.” This approach ensured systematic and comprehensive coverage of the research topic. This review examines the green synthesis and therapeutic potential of bimetallic nanoparticles, focusing on their production using plant extracts and other biological methods. It also evaluates the hazards and biological consequences associated with their widespread presence in biological tissues. Researchers have conducted various studies on Ag/ZnO bimetallic nanoparticles using physical, chemical, and biological synthesis methods, exploring their green synthesis approaches, physicochemical properties, structural characteristics, and safety in vivo and the environment. Among these methods, biosynthesis, particularly plant-based synthesis, has emerged as the most effective and sustainable strategy. Plant-derived Ag/ZnO bimetallic nanoparticles exhibit exceptional characteristics and performance, making them highly effective for biomedical, antibacterial, therapeutic, and environmental applications. Their modified morphology further enhances their functional properties, significantly improving their efficacy across multiple disciplines. Nanoparticles synthesized through green synthesis methods hold great potential for the development of novel antibacterial drugs. The market for Ag/ZnO nanoparticles has expanded significantly, evolving into a major economic sector. With the growing demand for applications, plant-derived nanoparticles require rigorous experimentation and large-scale research to support vaccine development and advancements in human health. Plant-based synthesis offers a sustainable and economically viable alternative for nanoparticle production, reducing dependence on chemically synthesized materials. Therefore, extensive and in-depth research on plant-synthesized bimetallic Ag/ZnO nanoparticles is essential to overcome the limitations associated with chemically synthesized nanoparticles. This research will provide a scientific foundation for their broader applications and contribute to human health and environmental safety.